2016
DOI: 10.11648/j.mc.20160403.11
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Isotopic Abundance Ratio of Biofield Energy Treated 1,4-Dichlorobenzene Using Gas Chromatography-Mass Spectrometry (GC-MS)

Abstract: Abstract:The objective of the current study was to evaluate the effect of biofield energy treatment on the isotopic abundance ratios of P M+1 /P M , P M+2 /P M , P M+3 /P M and P M+4 /P M in p-DCB using gas chromatography-mass spectrometry (GC-MS). The p-DCB was divided into two parts -one part was control sample, and another part was considered as the treated sample which was subjected to biofield energy treatment (The Trivedi Effect ® ). T1, T2, T3, and T4 were referred the biofield treated p-DCB having anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…The relative intensity of the peak in the mass spectra is directly proportional to the relative isotopic abundance of the molecule and the isotopic abundance ratio analysis was followed by the scientific literature reported [36][37][38][39] Where, IAR Treated = isotopic abundance ratio in the Biofield Energy Treated sample and IAR Control = isotopic abundance ratio in the control sample.…”
Section: Isotopic Abundance Ratio Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The relative intensity of the peak in the mass spectra is directly proportional to the relative isotopic abundance of the molecule and the isotopic abundance ratio analysis was followed by the scientific literature reported [36][37][38][39] Where, IAR Treated = isotopic abundance ratio in the Biofield Energy Treated sample and IAR Control = isotopic abundance ratio in the control sample.…”
Section: Isotopic Abundance Ratio Analysismentioning
confidence: 99%
“…Scientific literature [37][38][39]45] reported that the vibrational energy is closely related with the reduced mass (µ) of the compound and the alteration of the vibrational energy can affect the several properties like physicochemical, thermal properties of the molecule. The relation between the vibrational energy and the reduced mass (µ) for a diatomic molecule (Equation 1) is expressed as below [42,45]…”
Section: Isotopic Abundance Ratio Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…This process is known as The Trivedi Effect ® -Biofield Energy Healing Treatment [17,18] ) has been drawn attention more in the recent times for its scientifically measurable capability to transform the characteristic properties of a wide varieties living and non-living substances such as animals [20], cancer cells [21], microbes [22,23], plants [24,25], medium [26,27], materials [28,29], pharmaceuticals [30,31], nutraceuticals [32,33], organic compounds [34,35]. The scientific study indicated that Biofield Energy Healing Treatment (The Trivedi Effect ® ) might be an alternate method for increasing or decreasing the natural isotopic abundance ratio of the substances [36][37][38][39]. The stable isotope ratio analysis has the wide applications in several scientific fields for understanding the isotope effects resulting from the variation of the isotopic composition of the molecule [40,41].…”
Section: Introductionmentioning
confidence: 99%